Numerical simulation of dispersion and distribution behaviors of hydrogen leakage in the garage with a crossbeam. (December 2019) - Li, Yunhao; Jiang, Juncheng; Yu, Yuan; Zhang, Qingwu
A three-dimensional computational fluid dynamics simulation model resolved by the unsteady Reynolds-Averaged Navier–Stokes equations was developed to predict hydrogen dispersion in an indoor environment. The effect of the height of the crossbeam (Hc) on hydrogen dispersion and distribution behaviors in a four-car garage was numerically investigated under fully confined and natural ventilation conditions. For the fully confined condition, the garage was almost completely filled with a flammable hydrogen cloud at t =600 s. In addition, the volumetric ratio of the flammable region, thickness of the hydrogen stratification, and hydrogen mole fraction all increased as Hc increased. When two symmetric ventilation openings were set up, the volumetric ratio of the flammable region decreased by 50% at t =600 s. Moreover, Hc had evident influence on the vertical distribution of hydrogen mole fraction. In addition, there existed little explosion hazard under the height of 1.6 m. The results show that Hc was a non-negligible factor for the safety design of hydrogen in the garage and Hc=0.12 m was the optimal height of the crossbeam. Furthermore, the ventilation system in the present study cannot completely eliminate the risk of hydrogen explosion. The present risk assessment results can be useful to analyze safety issues in automotive applications of hydrogen.